The racial and linguistic elementas of the English language - Fearon, Estella May (My University, 1903)
Introduction: The English tongue is a member of a great group or family, embracing many seemingly remote tongues. This family originally occupied a large portion of Asia and nearly the whole of Europe. The name given to it at the present time is the Indo-European or Aryan Family. The place where this language was first spoken is not definitely known, although its first home is supposed to have been in parts of southwestern Asia and eastern Europe. Scientific study of the Indo-Europe4an family shows that all branches of it contain certain grammatical and root forms which bear a strong resemblance tone another. For this reason they are supposed to have sprung from a common source. According to the similarity or nearness of relationship the Indo-European family has been divided in to the following branches. I. The Indian. This branch includes the Gypsy, Hindi, Hindustani and Mahratti. Its greatest representative is Sanskrit. The earliest form of the Indian branch goes back to about two thousand years before the Christian era, and its latest except the Sanskrit to about three centuries before that epoch. The Sanskrit is spoken and written by a small priesthood in a limited section, to the present day. The Indian is the oldest known language belonging to the great Indo-European family and probably comes nearest to the primitive speed of all known languages. II. The Iranian. Including as its principal existing representative the Modern Persian and as its ancient branches the Parsi, and the Cuneiform Inscriptions containing records of the reign of Darius, Xerxes and other Persian kings from about 500 B.C. III. The Hellenic. so named from the Hellenes, the inhabitants of Hellas. This embraces ancient Greek and the Atalic, the Doric, the Ionic and particularly the Attic dialects. The existing from is Modern Greek. IV. The Slavonic or Slavo-Lettic.
Citation: Fearon, Estella May. The racial and linguistic elementas of the English language. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Iranian Inclusions; Hellenic Inclusions; Slavonic or Slavo-Lettic; Theses